2019
DOI: 10.1007/s10753-019-01148-1
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 Induced Stromal Cell–Derived Factor-1 and Profibrotic Factor in Keloid-Derived Skin Fibroblasts via the STAT3 Pathway

Abstract: The pathogenesis of keloids has not been elucidated, and the disease is thought to be caused by abnormal secretion of proinflammatory mediators and irregular responses to other inflammatory signals mediated by keloid fibroblasts (KFs). In this study, we investigated whether a local increase in interleukin IL-17 in keloid tissues stimulates the production of stromal cell–derived factor-1 (SDF-1) in KFs causing further recruitment of IL-17-producing T helper 17 (Th17) cells, which subsequently creates a positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 13 publications
2
56
0
Order By: Relevance
“…PI3, CCL20, S100As) axes, as well as the JAK/STAT signaling molecule JAK3. The up-regulation of Th17 markers expands upon prior reports demonstrating a role of Th17 mediators in keloids (11,55). Additionally, our results suggest that, similar to other fibrotic diseases (56), the Th1 axis is also involved to keloid pathogenesis.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…PI3, CCL20, S100As) axes, as well as the JAK/STAT signaling molecule JAK3. The up-regulation of Th17 markers expands upon prior reports demonstrating a role of Th17 mediators in keloids (11,55). Additionally, our results suggest that, similar to other fibrotic diseases (56), the Th1 axis is also involved to keloid pathogenesis.…”
Section: Discussionsupporting
confidence: 87%
“…Our group recently examined a few Th2 markers in keloids (20), while another study found increases for the IL-17/IL-22-induced products, S100A7 and hBD2 (53). Additionally, dysregulation of the IL-17/IL-6 axis (11) and/or JAK/STAT-signaling (54,55) have also been investigated. The present study expands on prior investigations and provides a comprehensive molecular profiling of keloids, identifying a significant immune component in both lesional and non-lesional skin, as well as linking keloids with fibrosis and cartilage/bone-differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we also conducted an iTRAQbased quantitative proteomic analysis, and the data reveals that 295 proteins were downregulated and 305 proteins were upregulated in OGD-ECs compared to normal control ECs (data not shown). It was known that several factors such as IL-17, HIF-1α, E2, and FGF-2 could regulate the expression of CXCL12 [36][37][38][39], and we are performing an in-depth study for the mechanisms of CXCL12 increase in EPCs in another study. EPCs-CM or EPC transplantation improves the white matter integrity, decreases capillary breakdown, and inhibits apoptosis after traumatic brain injury (TBI) [12,40].…”
Section: Discussionmentioning
confidence: 99%
“…Specimens were obtained from ten patients (5 males and 5 females, aged 25–48 years) with keloid and the adjacent normal skin tissues, cell cultures were established as described previously. 9 Briefly, the isolated skin specimen was placed in sterile petri dishes and washed with phosphate-buffered saline (PBS), then incubated with 2.5 mg/mL dispase II (Hoffman-La Roche, Indianapolis, IN, USA) overnight at 4°C. On the second day, the specimen was removed from the epidermis and subcutaneous tissues, and the dermis was manually cut as much as possible and then seeded in 6-well plates.…”
Section: Methodsmentioning
confidence: 99%